Achilles steel?: Investigating corrosive capital in the Smederevo Železara privatization - Ben Reade (Journal of Regional Security, 2023)
The term "corrosive capital" has become a popular phrase in Serbia and across the Western Balkans used to describe opaque and scandalous foreign investments that are believed to enable state capture. Particularly in Serbia, existing approaches to corrosive capital have certainly identified which investments are problematic. However, there is still a lack of understanding about which key actors are culpable for corrosive investments and the practices that enable them. Responsibility is often binarily assigned, either to the Vučić regime or non-Western actors. This paper, however, more rigidly explores the networked structures and practices that bring about corrosive capital. Through the development of an analytical framework and an investigation of the Smederevo Železara privatization, this paper argues that corrosive capital is a multi-level phenomenon enabled by interactions between various domestic and foreign actors that leads to state capture. This paper particularly notes how the combined effect of actions taken by Serbia, the EU, and the Chinese firm HBIS has facilitated corrosiveness with respect to the Železara privatization.